Validity and reliability of a new wearable chest-strap device to measure respiratory frequency in elite soccer athletes - Di Paco, A.; Bonilla, D. A.; Perrotta, R.; Canonico, R.; Cione, E.; Cannataro, R. (28th Annual Congress of the European College of Sport Science, 4-7 July 2023, Paris, France, 2023)
INTRODUCTION: The assessment of the respiratory frequency (fR) has practical importance in monitoring training progress in competitive athletes, especially during exercise. This study aimed to validate a new wearable chest-strap (wCS) device to measure fR against ergospirometry as a criterion device in healthy adults. The gold standard for performance evaluation remains the cardiopulmonary exercise test. However, it remains a test that cannot be applied in daily training practice